An Exemption for Sincere Believers: The Challenge of Alberta v. Hutterian Brethren of Wilson Colony - Weinrib, Sara (McGill Law Journal / Revue de droit de McGill, 2011)
In Alberta v. Hutterian Brethren of Wilson Colony, the Supreme Court of Canada reconfigured its approach to section 1 of the Canadian Charter of Human Rights and Freedoms by holding that the final step of the R. v. Oakes test—the requirement of proportionality between a measure’s salutary and deleterious effects—provided the critical framework for its analysis. The author suggests that the Court’s emphasis on the last step of the Oakes test was not the most appropriate response to the specific minimal impairment argument Alberta presented. Alberta argued that the reason it could not safely offer an exemption from its licence photo requirement to Hutterites who objected to photos on religious grounds was because Syndicat Northcrest v. Amselem restricted government inquiries into the sincerity of religious beliefs. Ontario intervened in support of Alberta’s concerns. Although the Court did not address this minimal impairment argument, the author argues that it reflects an unnecessarily strict reading of how Amselem’s guidelines would apply in this context. In support, the author presents an exemption that would have cohered with Amselem and achieved Alberta’s safety objectives. The author then argues more broadly that the provinces’ concerns in Hutterian Brethren demonstrate the critical role the minimal impairment step of the Oakes test plays in generating solutions to clashes between laws of general application and minority religious practices. The Court’s new emphasis on the proportionate effects test, in contrast, may unfortunately discourage both parties from formulating potentially innovative alternatives.